First case of isolation of Nocardia wallacei reported in Mexico. (November 2016) - González-Nava, J.; Sánchez-Herrera, K.; Ramírez-Durán, N.; Sandoval, H.
Abstract: Nocardia species are aerobic, Gram-positive bacteria with branched filaments reported as opportunistic microorganisms associated with infectious diseases of the skin. We report the isolation of N. wallacei in Mexico from a 43-year-old man, an HIV-positive construction worker who sought care for difficulty breathing and abundant sputum.